Connectivity among Norway rat subpopulations (Rattus norvegicus) at poultry farms in Exaltación de la Cruz, Buenos Aires, Argentina - Gomez Villafañe, Isabel Elisa (2019)
Despite of the substantial economic and human health problems produced by rodents of the genus Rattus almost nothing is known about its actual dispersal. In the present study we analyze the genetic subdivision of R. norvegicus inhabiting poultry farms of Buenos Aires, Argentina, and the relation between geographic and genetic distances by means of variation in microsatellite loci. We genotyped 40 rats captured between April-06 and June-07 from nine poultry farms distributed in an area of 110 km2 . No genetic subdivision was found among di erent poultry farms. This result supports the hypothesis of high connectivity between R. norvegicus inhabiting poultry farms in Buenos Aires. Because this species is a known host of diverse zoonosis as leptospirosis and trichinosis, our results point out that there is a great risk of transmission for distances lower than 12 km. Health control and preventive measures should therefore be applied simultaneously in all nearby poultry farms.